CONTEMPORARY PEDAGOGY FOR THE ADULT LEARNING - Celli, Lynne M; Young, Nicholas D (PUPIL: International Journal of Teaching, Education and Learning, 2017)
The purpose of this article is to discuss contemporary educational pedagogy for the 21st century adult student (commonly called andragogy) with attention to current learning styles theory. As the roles and responsibilities of current faculty continue to develop it is important to also focus on how learning styles theory and adult learning theory can be used to enhance andragogy in universities and colleges. This article will also address research on andragogy and its practical application to teaching, as well as student strategies for success. As the role of faculty continues to evolve, higher education needs to be responsible and responsive in preparing to address the diverse, contemporary and future challenges of the 21st teacher and student.